Gynecomastia Surgery: Liposuction Alone versus Liposuction with Endoscope-Assisted Glandular Excision—A Comparative Study - Ali, Sheikh Sarfraz; Ahmed, Imran; Khurram, Mohammed Fahud; Rehman, Noha; Abhishek, Rupraj (Indian Journal of Plastic Surgery, 2025)
Gynecomastia, affecting around 30% of young males, has seen evolving surgical treatments, transitioning from traditional excision methods to contemporary techniques like liposuction. Emotional distress persists when glandular tissue is inadequately addressed, prompting exploration of combined liposuction and glandular excision procedures.Patients undergoing gynecomastia surgery over a period of 2 years were assessed, considering their demographics, medical history, and gynecomastia grade. Surgical procedures involved liposuction alone or with glandular excision. Endoscopy was used to assess the presence of fibroglandular tissue and the need for glandular excision. Postoperative assessments, clinical photography, and patient questionnaires spanned a 6-month follow-up.Thirty-two breasts (17 in liposuction alone and 15 in liposuction with glandular excision groups) were included. Liposuction alone led to bruising and two hematomas, and “puffy nipples” necessitating one redo surgery. Glandular excision resulted in four cases of crater deformity and one case each of superficial skin necrosis, hematoma, and seroma. Cosmetic evaluations showed similar outcomes, with the liposuction alone group having higher redo surgery rates.This study finds that combining liposuction with glandular excision delivers comparable cosmetic results to liposuction alone for gynecomastia. Despite added complexity, the combined approach proves effective and helps in decision-making, emphasizing the need for tailored techniques and ongoing research to optimize treatment strategies.
Keywords: gynecomastia; liposuction; aesthetic outcomes; peri-areolar glandular excision; patient satisfaction